Energy management in industry : a case study on the brewing industry - De Villiers, Mark Graham (Energy Research Centre, 2016)
The industrial sector is the main energy user in South Africa, using about half the national total, and compared to most other industrialised countries South Africa has a high in_dustrial energy intensity, thus necessitating improved industrial energy management. The malt brewing industry was chosen as a case study industry to illustrate the potential for improved energy management in industry. Ohlsson's brewery in Cape Town was analysed in detail and energy management improvements identified for that brewery were ·expanded to include the malt brewing industry in general, by comparing Ohlsson's brewery to other breweries in South Africa. It was found that energy requirements at Ohlsson's Brewery could be reduced by 12-20%, by the implementation of economically feasible energy management schemes. However, mainly because of discrepancies in coal prices between Ohlsson's Brewery and most other breweries in South Africa, energy requirements for the brewing industry in general can be reduced by 7-13%. This translates to be a monetary saving of R242 000-R486 000/month, which is evenly spread between coal, electricity, and maximum demand savings. No single large energy saving scheme was identified, but the potential. savings are due to a number of schemes. The potential energy savings identified in this study exclude the savings as a result of the implementation of process sensitive schemes, which were considered beyond the scope of this study. Nevertheless some process sensitive schemes, associated with boiling in the brewhouse, could result in substantial savings. The energy usage target identified for South African breweries is higher than current energy requiiements for breweries in the Britain and Germany when climatic and operational constraints are taken into account. This is because Britain and Germany have higher energy costs relative to production costs, government incentive schemes for reducing energy usage, and more stringent environmental legislation often necessitating the recovery of brewhouse vapours.